2019
DOI: 10.1038/s42254-018-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

3D metamaterials

Abstract: License: Article 25fa pilot End User Agreement This publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
446
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 798 publications
(449 citation statements)
references
References 201 publications
1
446
0
2
Order By: Relevance
“…We present the design, synthesis, and testing of an in-vivo 3D shape tissue engineering material baed on meta-material physics. 23,24 Numerical simulation allowed us to translate the unmet clinical need of a shapeable soft tissue implant 8,11,16 into a set of engineer-able mechanical and geometric parameters. With the elastic, porous, and injectable (EPI) biomaterial, we achieved desired shape-stable, softening, and yielding behaviors, along with substantial porosity and a tissue-matching mechanical response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We present the design, synthesis, and testing of an in-vivo 3D shape tissue engineering material baed on meta-material physics. 23,24 Numerical simulation allowed us to translate the unmet clinical need of a shapeable soft tissue implant 8,11,16 into a set of engineer-able mechanical and geometric parameters. With the elastic, porous, and injectable (EPI) biomaterial, we achieved desired shape-stable, softening, and yielding behaviors, along with substantial porosity and a tissue-matching mechanical response.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we reconcile injectability, shapeability, and long-term volume stability by a radically novel approach: an injectable meta-material 23 . Mechanical meta-materials obtain unusual properties by their mere geometry 23,24 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are different routes to elastic cloaking which have been listed in [4,5], and we shall focus here on one of these based on the concept of unconventional effective dynamic properties enabling both minor symmetry breaking in the rank-4 elasticity tensor as well as non vanishing rank-3 and 2 tensors in the Willis model [6] near resonant frequencies of certain types of stress-free inclusions shaped as swiss-rolls. Swiss-rolls were introduced in the context of electromagnetic metamaterials for artificial chirality [7], and such magneto-optic coupling recently found a counterpart in elasticity [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Since the prediction of negative refractive indices [4] and their experimental realization [5], many fundamental studies have been performed and possible applications have been demonstrated, which include perfect lenses [6], hyperlenses [7], optical cloaks [8], etc. The fabrication of bulk metamaterials is challenging [9]. However, metasurfacestwodimensional arrays of sub-wavelength structuresare easier to fabricate and in many cases sufficient to provide the function of a frequency-selective filter, a polarizer, a lens or a similar optical element by merely a very thin structured layer [10 -38].…”
Section: Introductionmentioning
confidence: 99%